(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The article reveals the essence, content and features of investment projects. The main elements and classification features of investment projects by content, objectives, scale, implementation time, industry focus and proposed financing scheme are analyzed. Based on the conducted research, scientific conclusions were formulated and recommendations for the effective implementation of investment projects in Uzbekistan were developed.